2005
DOI: 10.1152/ajpregu.00596.2004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in rat soleus muscle phenotype consecutive to a growth in hypergravity followed by normogravity

Abstract: Picquet, F., V. Bouet, L. Cochon, M. Lacour, and M. Falempin. Changes in rat soleus muscle phenotype consecutive to a growth in hypergravity followed by normogravity. Am J Physiol Regul Integr Comp Physiol 289: R217-R224, 2005. First published March 17, 2005; doi:10.1152/ajpregu.00596.2004.-It has been demonstrated that a long-term stay in hypergravity (HG: 2G) modified the phenotype and the contractile properties of rat soleus muscle. The ability of this muscle to contract was drastically reduced, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The effects of a hypergravity environment may be transduced by vestibular activation, bone and skeletal muscle load, body-fluid shift, and pressure changes, which then elicit physiological and pathophysiological responses (1,8,22,25). These putative afferent mechanisms could contribute to hypergravity-induced transient hypophagia.…”
mentioning
confidence: 99%
“…The effects of a hypergravity environment may be transduced by vestibular activation, bone and skeletal muscle load, body-fluid shift, and pressure changes, which then elicit physiological and pathophysiological responses (1,8,22,25). These putative afferent mechanisms could contribute to hypergravity-induced transient hypophagia.…”
mentioning
confidence: 99%
“…Chronic centrifugation was expected to induce a shift to a slower type of fibre in the load‐bearing muscles, as has previously been reported in the soleus of rats conceived and reared in HG (Picquet et al ., ; Bozzo et al ., ); however, the proportion of fibres in the soleus did not change. The possibility that the animal's muscles adapted to earth gravity over the long period between training and testing is not consistent with previous reports of persistent change even after 120 days (Picquet et al ., ). We propose that the change in fibre typology was apparent in the rats in Picquet's study because they were centrifuged for a period of 100 days; in our study, the period of centrifugation was shorter (3 weeks), and was potentially not sufficient to induce a lasting change in fibre typology, because the adaptation of load‐bearing muscles to HG is known to be a slow process.…”
Section: Discussionmentioning
confidence: 97%
“…As previously mentioned, Picquet et al (2002) showed that soleus antigravity muscle of rats conceived, born, and reared in HG until 100 days expressed 100% slow myosin phenotype. In a subsequent study, the same authors showed that in these animals, NG from 100 days to 115 or 220 days did not transform the muscle phenotype, suggesting the existence of a critical period in muscle phenotype determination (Picquet 2005). One may hypothesize that these persisting changes in descending pathways and muscle properties during subsequent exposure to NG were likely to lastingly influence the cortical integration of proprioceptive inputs, and thus the corresponding representations in the S1 map.…”
mentioning
confidence: 91%